Efficient data delivery based on content-centric networking for Internet of Things applications - Mahfuzur R Bosunia; Kamrul Hasan; Nazib Abdun Nasir; Seonghyuck Kwon; Seong-Ho Jeong (International Journal of Distributed Sensor Networks)
Content-centric networking is a new networking paradigm for efficient data distribution in various environments including wireless sensor networks. It is likely that everything which benefits from networking will be connected. Recently, we have seen a huge proliferation of heterogeneous wireless devices, sensors, and distributed applications. These devices may generate a vast amount of time-constrained data. Content-centric networking is greatly useful to increase the data availability and the efficiency of data delivery. Internet of Things will enable all the communication devices to be interconnected and make the data generated by or associated with devices or objects globally accessible. In this article, we propose a possible architecture, necessary components, and related mechanisms for efficient data delivery in the wireless Internet of Things environment, which is based on content-centric networking. We also present simulation results to show the feasibility of the proposed architecture.